A state‐of‐the‐art review on the impact of fast EV charging on the utility sector. Issue 4 (19th November 2021) - Shariff, Samir M.; Alam, Mohammad Saad; Hameed, Salman; Khalid, Mohd Rizwan; Ahmad, Aqueel; Al‐Ammar, Essam A.; Alsaidan, Ibrahim; Alrajhi, Hasan
Abstract: Deployment of fast‐charging stations for electrified transportation is currently one of the limiting factors in the commercial deployment and paradigm shift of the mobility sector. The rapidly increasing demand for electric vehicles (EVs) brings the demand for accessible and affordable charging infrastructure. The commercial EV fast‐charging load profile depends on the customer's EV charging demand, which poses challenges in determining the overall peak profile. This could lead to unprecedented challenges of harmonic disruption, system losses, supply‐demand balance, and grid reliability. The emergence of bidirectional charging infrastructure and the realization of controlled charging strategies in coordination with the cumulative contribution of renewable energy resources could potentially reduce the challenge of utility grid stability and reliability shortly. Furthermore, the parallel development of smart grid technologies has promising features. This paper aims to provide a comprehensive state‐of‐the‐art review of the major challenges of the utility grid in the swift adoption of fast charging infrastructures available in the open literature, as well as the sustainable implications and potential safety measures. Furthermore, the potential solutions and best practices for the synchronization of electrified transportation with the emerging ecosystem of renewable power systems and various controlled charging strategies are reviewed in detail.